Thailand Financial Sector Assessment Program : Thailand Securities Depository of the CPSS/IOSCO Recommendations for Securities Settlement Systems - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
Securities settlement systems should have a well-founded, clear and transparent legal basis in the relevant jurisdiction. The laws, regulations, rules and procedures governing the operations and activities of Thailand Securities Depositories (TSD) are public and accessible to participants. In particular, participants receive comprehensive documentation covering the rules, requirements, procedures and instructions of TSD. This documentation is available on request and is accessible on the TSD website. The public authorities' regulations are also available to the general public on the websites of the Ministry of Commerce (MoC), the Securities and Exchange Commission (SEC) and the Bank of Thailand (BOT). It is recommended to implement adequate legal measures that ensure the netting arrangement is legally protected even in the event of the insolvency of a participant.